Expansion of the Foramen Ovale in Patients With Cerebrospinal Fluid Leak or Encephalocele. Issue 7 (August 2022) - Curry, Steven D.; Granger, Kleve W.; Richman, Evan H.; Liu, Collin; Moore, Gary F.; Barnes, Christie A.; Surdell, Daniel L.; Hatch, Jonathan L.
Abstract : Objective: Spontaneous cerebrospinal fluid (CSF) leaks are associated with elevated intracranial pressure and idiopathic intracranial hypertension (IIH). Skull base erosion and widening of the foramen ovale have been reported in patients with IIH. This study sought to investigate changes in the size of the foramen ovale and foramen spinosum in patients with IIH, spontaneous CSF leak, and encephalocele. Study Design: Retrospective cohort study. Setting: Tertiary care academic medical center. Patients: Adult patients treated from 2014 to 2018 with computed tomographic imaging of the head and who were diagnosed with IIH, encephalocele, or CSF leak. Intervention: Two blinded observers measured the long and short axes of the foramen ovale and foramen spinosum on axial computed tomographic images. Measurements were used to calculate the approximate elliptical cross-sectional area of the foramina. Main Outcome Measures: Length, width, and area of the foramen ovale and foramen spinosum. Results: A total of 264 patients were identified meeting the inclusion criteria and were placed into three groups. There were 170 patients with IIH, 48 with spontaneous CSF leak or encephalocele (CSF/E group), and 46 with traumatic or iatrogenic CSF leak (control group). Mean foramen ovale short axis (4.85 ± 1.00 mm) and cross-sectional area (30.17 ± 9.25 mm 2 ) in the CSF/E group were significantly increased compared with measurements in patients with IIH or the control groups. Foramen ovale size was positively correlated with age in the CSF/E group. No significant difference in foramen spinosum size was found. Conclusion: Skull base defect resulting in spontaneous CSF leak or encephalocele is associated with enlargement of the foramen ovale on axial computed tomography.